Extradition and Asylum in the Light of the Protection of Human Rights of Migrants - Jovašević, Dragan (Zbornik Instituta za kriminološka i sociološka istraživanja, 2018)
The rule is that in all modern criminal legislation, and so in the legislation of the Republic of Serbia, the competent court, after a criminal procedure, pronounces the type and measure of the sentence or other criminal sanction to each criminal responsible for the criminal offense. This rule applies both to a citizen of Serbia and to an alien as a perpetrator of a criminal offense. The law stipulates the conditions for exercising the protective function of the criminal law as well as the extradition institute. It is the provision of international legal assistance by a state to another state and its judicial authorities to bring to justice the perpetrator of the crime. This ensures the international community's solidarity in combating crime at a global level. However, there is a legally foreseen exception to this rule. It is applied in cases when a foreigner commits a criminal offense, provided that he / she is an asylum seeker. Therefore, asylum protects the human rights of foreigners (or stateless persons) from criminal prosecution for certain offenses based on discrimination of any kind. It is precisely the application of extradition and the right to asylum in the law of the Republic of Serbia, in light of the protection of human rights of migrants.